The Role of Active Constructive Feedback in Building Employee Performance (Case study at a private construction company in Indonesia 2018-2019) - Rony, Zahara Tussoleha; Yasin, Mahmuddin; Lubis, Fatimah Malini; Syarief, Faroman (International Journal of Psychosocial Rehabilitation, 2020)
–Feedback becomes an important part of the performance appraisal process. Feedback is one of the processes to explore the strengths of employees so that it is easier to identify many competencies and the potential of each employee. But the fact is that there are still many leaders who do not consider feedback as an important activity. This has an impact on improving individual performance. This paper aims to describe the activities of leaders at the managerial level in the technical division in the process of improving the performance of their members in 2018 at one of Indonesia’s private construction companies. Secondary data were obtained from individual development programs, assessment results, performance appraisal in 2017, while primary data were obtained from field notes, interviews and observations. To express this incident a qualitative case study method is used. The sampling technique is done by purposive and quota sampling and assigns 10 technical division employees as informants. Invalidating the findings of researchers involving the HR management team, leadership, HR practitioners The assessment process carried out by some leaders in assessing technical competencies, core competencies of the company and measuring key performance indicators employees are quite effective, but formal meaningful face-to-face activities have not been used optimally, especially in providing constructive active feedback. In the era of the Industrial Revolution, 4.0 leaders need to understand the philosophy of employee performance appraisal effectively. Based on these findings, human resource managers need to design effective feedback skills training and provide rewards to managers who carry out constructive feedback well.